Features of the organization of integration processes in agricultural food systems - L. O. Makarevich; A. V. Ulezko (Новые технологии, 2019)
The research is based on the hypothesis that the integration processes of business entities that interact economically and organizationally within the framework of technological and product chains are an objective form of the evolution of production relations and reflect the level of development of the system of intersubjective interactions. A set of measures related to the generalization of objectively existing motivations for the formation of a system of stable intersectoral interactions of entities, development of mechanisms for managing the development of integrated associations and balancing the economic interests of integrating agents are considered as the organization of integration processes.The complexity of organizing integration processes in the agri-food complex is determined by the combined influence of a complex of factors of various nature, which are recommended to be systematized in the context of three groups: economic, organizational, and technical and technological. In modern Russia the dominant form of integration is vertical integration, in which development priority is not to harmonize and balance the interests of integrating entities, which is typical for a contract form of integration, but to maximize return on invested capital and the amount of profit from the sale of final products due to full control over all parts of the technological chain and capital concentration, providing economies of scale and diversification of production.